COMMUNITY EMPOWERMENT MANAGEMENT THROUGH WASTE BANK IN KUTASARI VILLAGE AND WASTE BANK IN BOBOSAN VILLAGE BANYUMAS REGENCY - Sutikno, Chamid Chamid; Kurniasih, Denok (Journal of Sustainable Rural and Tropical Resources Development; Vol 3 No 1 (2025): Journal of Sustainable Rural and Tropical Resources Development (JSRTRD), 2025)
This study discusses the management of community empowerment at the Kutasari Village waste bank and Bobosan Village waste bank, Banyumas Regency. The purpose of this research is to describe the community empowerment management process at the Kutasari Village waste bank and Bobosan Village waste bank. The waste bank is a place for the community to manage and organize waste that has been sorted so that it can assist the village and community in managing and controlling waste management. The existence of a waste bank is to help handle waste management and to make people aware of a healthy, neat and clean environment. This study used descriptive qualitative research methods with primary and secondary data sources. Methods of data collection in the form of interviews, observation, and documentation. While the selection of informants was selected based on ability according to purposive sampling. The results of this study are seen from the first aspect of planning that in the planning process several strategies or stages are carried out including work program planning, outreach planning, and development planning. Second, the organization that in the management of the institution has formed an organizational structure and division of labor in accordance with duties and responsibilities. The third implementation is by carrying out excellent programs such as money savings and gold savings as well as programs for training in making crafts such as making eco brick, eco print and eco enzyme. The four supervisions at the waste bank are internal supervision between members of the waste bank and also involving external parties, in this case the village district.